Psychometric properties of the Quiet Ego Scale (iQES) within the Italian cultural context - Bernabei, Laura; Silvestrini, Cristiana; Grimaldi, Lucrezia Andrea; Piserchia, Valentina; Riggio, Francesco; Marino, Giovanni; Valente, Donatella; Pompili, Enrico (Frontiers in Psychology, 2024)
The quiet ego indicates a more compassionate conception of self-identity that integrates others into the self by lowering the intensity of the ego and enhancing the awareness of the present moment. The Quiet Ego Scale - QES is a 14-item self-report measure of quiet ego - is composed of the following four psychological domains: detached awareness, inclusive identity, perspective taking, and growth. The present study aimed to test the psychometric properties of the Quiet Ego Scale within the Italian cultural context (iQES). A total of 160 Italian university students aged 20-42 (M=22.85; DS=3.41) completed the measures of the iQES and of the other psychological dimensions. The psychometrics properties were assessed via its internal consistency, test-retest reliability, and construct validity through comparisons with other psychological correlated measures. Psychometric properties of iQES were confirmed from analyses. As previous studies, the quiet ego was positively associated with the indicators of resilience (p <.01), happiness (p <.05), self-esteem (p <.01), psychological wellbeing (p <.01). Results were discussed in the light of possible uses of the iQES in the field of mental health, in the light of ameliorating adherence to psychological therapies, and recover psychological and social well-being. The results demonstrated the good psychometric properties of the iQES in terms of measuring the quiet ego construct. Our results contribute to increase the literature on the validity of the iQES, and the multidimensional nature of the quiet ego construct.